Analisis Faktor yang Berhubungan dengan Waktu Tunggu Pemeriksaan Foto Toraks Pasien Rawat Jalan di Instalasi Radiologi Rumah Sakit Dr. Mohammad Hoesin Palembang Tahun 2015 - Yusri, Muhammad (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2015)
Department of Radiology Dr. Mohammad Hoesin hospital in Palembang 2014, many patients perform chest x ray examination, whom were patients radiographic outpatient. The waiting time radiographic services in RSMH not in accordance with the Standard Minimum Service Hospital less than 3 hours. This study aims to determine the factors associated with waiting time chest X-ray. This research was conducted by measuring the waiting time to 68 selected respondents The result showed radiographic waiting time 184.44 minutes. Based on statistical test found the waiting time in the reading room is the photo that most affect the length of waiting time radiographic.